Biossorção de corante têxtil azul marinho direto 251 utilizando bagaço de malte: cinética, equilíbrio e dessorção - Furtado, Damaris Fidelis (2018)
In the present work, the use of malt bagasse (BM), a residue from the brewing industry, was studied as a biosorbent in the adsorption of textile dye (Azul Marinho Directo 251). The BM was subjected to successive washes, drying at 105 °C and separated in granulometry higher than 600 m, being denominated BMLS. The biosorbent was characterized according to its physical-chemical properties, pHpcz and functional groups by infrared spectroscopy. Dye adsorption and desorption experiments were performed in the BMLS in a batch system. In the adsorption, the influence of the pH of the solution on the dye removal, the kinetics and the adsorption isotherm at different temperatures (20, 30 and 40 °C) were studied. The best pH value for the adsorption of the dye by BMLS was 5.3. In the kinetic study, the model that best represented the experimental data was pseudo-second order. The Freudlich model was the one that best represented the experimental data, presenting a maximum adsorbed quantity value of 13.10, 18.36 and 16.52 mg g-1, at temperatures of 20, 30 and 40 ºC, respectively. In the desorption, the use of different eluent solutions, the kinetics and the desorption isotherm at the temperature of 30 °C were studied. The NaOH solution 0.005 mol L-1 showed better desorption of the BMLS, with removal of 75.44 %. Desorption kinetics was represented by the pseudofirst-order model. The desorption isotherm showed to be unaffected by the concentration of the solution from 26.85 mg g -1. Adsorption/desorption cycles were performed to verify the reusability of the BMLS in the adsorption of the dye. Adsorption and desorption have been observed to decrease over the cycles indicating a strong bond between the dye and the surface of the BMLS. In this way, the BMLS presented as a good alternative to be used as a biosorbent in the removal of the dye, and it can be used in the treatment of textile effluents.